Light Induced Kinetic Studies of Oxidative Degradation of Malachite Green - Mostafizur Rahman, M.; Saha, R.; Ahmed, B.; Maria Rahman, M.; Afsar Uddin, M.; Yusuf, M.A.; Hasnat, M.A. (Asian Journal of Chemistry, 2010)
Oxidative degradation of malachite green was performed in presence of Fe(III) + H2O2 mixture in dark and in light. The UV radiation completely mineralized the dye molecules where the degradation rate was decreased in the order of UV > visible > dark. Malachite green molecules showed optimum colour in the pH range of 3.8-5.9. The effective Fenton activity was noticed at [H2O2]/[Fe(III)] ratio of 7.01. The degradation rate was positively influenced by the temperature where the activation energy degradation was estimated as 16.83 kJ mol-1. A maximum 86 % degradation was achieved at 45 ºC.